Productivity and water suppression in different beans (Phaseolus vulgaris L.) phenological stages - Miorini, Thomas Jose Justo [UNESP]; Saad, João Carlos Cury [UNESP] (My University, 2012)
Common Bean (Phaseolus vulgaris L.) is widespread in the social and economic scene in Brazil, as well it is Brazilian population main dish, and it also helps small and medium farmers' income. The objective of this study was to compare the productivity performance of common bean Carioca - IAC Alvorada with irrigation suppression in each of the five phenological phases. The experiment was conducted in plots in a greenhouse at College of Agronomical Sciences, São Paulo State University (UNESP), Botucatu - SP. The hypothesis is that if the water supply is suppressed in one of the five development stages of irrigated common beans, the yield reduction would be at least 20%. The treatments consisted of suppression irrigation in one of the five development stages (stage V1 to V3, stage V4 to early flowering, flowering stage, pod formation stage and pod filling stage) compared with the irrigation at all stages and suppression of irrigation at all stages, with seven treatments and four replications. The treatments most affected by water suppression were those which suffered suppression of irrigation during the vegetative phase and flowering stage. Treatments with water suppression in all stages, and suppression during the phases (stage V1 to V3, stage V4 to early flowering, flowering stage, pod formation stage and pod filling stage) showed yield reduction of approximately 95%, 55.1%, 49.5%, 63,1%, 30.2% and 35.6%, respectively, when compared to treatment with irrigation all stages. All treatments considered confirmed the hypothesis.
Keywords: Irrigation suppression; Phaseolus vulgaris L.; Phenological phases; Production; Botucatu; Common beans; Development stages; Early-flowering; Filling stage; Flowering stage; Formation stage; Phaseolus vulgaris; Phenological stage; Productivity performance; Water suppression; Yield reduction; Phenols; Productivity; Water supply; Irrigation